NANOFOSILES CALCAREOS DE LA FORMACION MAN AIKE (EOCENO, SUDESTE DEL LAGO CARDIEL) SANTA CRUZ, ARGENTINA (Ameghiniana, 2013)
Calcareous nannofossils from Man Aike Formation are described and illustrated from SEC-7 well, located near Cardiel Lake, Santa Cruz Province, Argentina. The nannoflora contains Neococcolithes dubius, Zigrhablithus bijugatus, Reticulofenestra umbilica, R. dictyoda, Braarudosphaera bigelowi, Transversopontis pulcher, T. obliquipons, Chiasmolithus grandis, Blackites spinosus, Micrantholithus attenuatus among the most representative species. They are typical of hyposaline-nearshoreenvironments. The age of the nannoflora is middle late Eocene and it is included in NP13-14 (Okada and Bukry, 1980) or in CPI5-18 (Martini) coinciding with the foraminiferal age determined for the same well.